-3b-4=-4b-3b

Simple and best practice solution for -3b-4=-4b-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3b-4=-4b-3b equation:


Simplifying
-3b + -4 = -4b + -3b

Reorder the terms:
-4 + -3b = -4b + -3b

Combine like terms: -4b + -3b = -7b
-4 + -3b = -7b

Solving
-4 + -3b = -7b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '7b' to each side of the equation.
-4 + -3b + 7b = -7b + 7b

Combine like terms: -3b + 7b = 4b
-4 + 4b = -7b + 7b

Combine like terms: -7b + 7b = 0
-4 + 4b = 0

Add '4' to each side of the equation.
-4 + 4 + 4b = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 4b = 0 + 4
4b = 0 + 4

Combine like terms: 0 + 4 = 4
4b = 4

Divide each side by '4'.
b = 1

Simplifying
b = 1

See similar equations:

| 75=30y+15 | | f(x)=.4x^5-2x^4+x^3-.5x+3 | | 4b+16a= | | 10x+11=3x-10 | | 21x-35=7y | | -16x^2+44x-24=0 | | 2x+51=7 | | 3+.4x=9y | | cos(2x)=.72 | | f(x)=2e^3x-1 | | 6x-12=5x-55-21 | | 4c-11+c=9 | | 2(2q+3)= | | t^2+6t+216=0 | | 14+15=7x+33 | | t^2+6a+216=0 | | 10x+60=12x | | (14/25)(-3/7)= | | 4(5u+1)= | | 6r-22=-47+r | | 14/25*(-3/7)= | | 224=90-x | | 5x=10-4y | | -3k+7+k=21 | | (7z+1)(3)= | | u+12=v | | 5.65x+16=31.9225+4x | | 1x-1y=1 | | 7x^2-1=-3x | | 32+100d=228 | | 2w=18-8 | | 3(x+2)=-9x+-7 |

Equations solver categories